2013
DOI: 10.1016/j.stem.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-Based Modeling of Late-Onset Disease via Progerin-Induced Aging

Abstract: Summary Reprogramming somatic cells to induced pluripotent stem cells (iPSCs), resets their identity back to an embryonic age, and thus presents a significant hurdle for modeling late-onset disorders. In this study, we describe a strategy for inducing aging-related features in human iPSC-derived lineages and apply it to the modeling of Parkinson’s disease (PD). Our approach involves expression of progerin, a truncated form of lamin A associated with premature aging. We found that expression of progerin in iPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
654
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 642 publications
(691 citation statements)
references
References 56 publications
(67 reference statements)
18
654
2
2
Order By: Relevance
“…In this regard, it is encouraging that (1) a model of human midbrain organoids produced neuromelanin, a dark pigment found in adult midbrains, after 2 months of culture;33 (2) long‐term cultured AD iPSC‐based brain organoids recapitulated both A β and tau pathology in a sequential manner 44. Further development in incorporation of other relevant cell types60 and accelerating maturation and/or aging in a dish67 would be extremely exciting and important.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is encouraging that (1) a model of human midbrain organoids produced neuromelanin, a dark pigment found in adult midbrains, after 2 months of culture;33 (2) long‐term cultured AD iPSC‐based brain organoids recapitulated both A β and tau pathology in a sequential manner 44. Further development in incorporation of other relevant cell types60 and accelerating maturation and/or aging in a dish67 would be extremely exciting and important.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 99%
“…The existence of genetic forms of premature aging diseases (including Hutchinson–Gilford progeria syndrome and Werner syndrome), provides us with another means of accelerating aging in a dish. Studies have shown that introduction of these disease‐causing genetic variants into otherwise wild‐type cells recapitulates many aspects of cellular aging 67. Taking this approach into 3D brain organoids may be potentially very useful for inducing adult or aged phenotypes within an experimentally feasible time frame.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 99%
“…For example, this issue of accelerated maturation has been partially resolved by mimicking aging in iPSCs by overexpressing progerin [36]. This process introduces an added variable and is not applicable to all cell types.…”
Section: Modeling Disease Using Human Cells In General and Psc-derivementioning
confidence: 99%
“…We have recently proposed that aging should be incorporated as an independent factor for the in vitro modeling of late-onset diseases. In a first such attempt, we hijacked the molecular mechanisms responsible for Hutchinson-Gilford progeria syndrome (HGPS), a premature aging disorder, to model late-onset degenerative features of Parkinson's disease (PD) in an iPSC-derived lineage (Miller et al, 2013).…”
Section: Introductionmentioning
confidence: 99%